The Didactic Engineering for the Math Olympics Teaching: Olympic Situations with Geogebra's Support - Ana Paula Rodrigues Alves Santos; Francisco Régis Vieira Alves (Universidad Distrital Francisco José de Caldas, 2018)
In this article, we intend to present a partial cut of a master's research, in which we describe, in a specific way, two phases determined by Didactic Engineering - ED in the context of the Mathematical Olympiads. Thus, we have the stages of preliminary analyzes and the construction of Olympic situations/a priori analysis. We emphasize in an Olympic situation that is described/structured with the support of GeoGebra software. Intervention through the proper exploitation of software provides the learner with opportunities to overcome certain difficulties/obstacles to an understanding or even conceptual construction in geometry. In this sense, the mentioned Olympic situation was experienced by students of the ninth year of elementary education II, from a private school in the state of Ceara, Brazil. The Olympic situation described proposes the possibility of the construction of metric relations in the triangle rectangle, content referring to the area of plane geometry. The ED is presented in this research, as a vision of complementarity that uses the theory of didactic situations - TSD. In this way, the described Olympic situation represents an alternative to classes directed to the math Olympics, their indication and structure, describes elements related to didactic mediation during the teaching and learning process, which emphasize details that make it possible to control and predict the possible student's actions, as well as, to provide the experience of more significant didactic situations for geometry study in the Olympic context.